2008
DOI: 10.1007/s11595-007-6779-2
|View full text |Cite
|
Sign up to set email alerts
|

Facile route to prepare TaC, NbC and WC nanoparticles

Abstract: By a novel solid-state reaction process using amorphous C 3 N 4 (a-C 3 N 4 ) and transition metal oxides as starting reagents, cubic TaC, NbC and hexagonal WC nanoparticles were successfully synthesized at 1150 ℃. The products were characterized by power X-ray diffraction (XRD), field-emission scanning electron microscope (FE-SEM), energy-dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM) and high-resolution TEM (HRTEM). The experimental results show that a-C 3 N 4 obtained by the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Nitrides of different transition metals have gained technological importance owing to their enhanced magnetic properties coupled with greater stability and corrosion resistance. 1,2 It is found that the physical and chemical properties of these materials are essentially dependent upon the nitrogen content in the system. 3 Iron nitrides, as a subject of research revealed that the nitrogen content is dependent on the diverse crystal structures and phases of iron nitrides, such as g-FeN (NaCl structure), x-Fe 2 N (orthorhombic structure), 3-Fe 3 N (hexagonal structure), g 0 -Fe 4 N and a 00 -Fe 16 N 2 (cubic structure).…”
mentioning
confidence: 99%
“…Nitrides of different transition metals have gained technological importance owing to their enhanced magnetic properties coupled with greater stability and corrosion resistance. 1,2 It is found that the physical and chemical properties of these materials are essentially dependent upon the nitrogen content in the system. 3 Iron nitrides, as a subject of research revealed that the nitrogen content is dependent on the diverse crystal structures and phases of iron nitrides, such as g-FeN (NaCl structure), x-Fe 2 N (orthorhombic structure), 3-Fe 3 N (hexagonal structure), g 0 -Fe 4 N and a 00 -Fe 16 N 2 (cubic structure).…”
mentioning
confidence: 99%
“…Darkening of the solid to red-brown was observed under vacuum, and sublimation of 1 (90-105°C at 10 -1 Torr) was accompanied by substantial decomposition (Ͼ 40 %). [61] Although WN x nanoparticles have been synthesized previously, [61][62][63][64] their synthesis at low temperature via pyrolysis has not been reported. Crystals suitable for X-ray structure determination were obtained by vapor diffusion of pentane into a concentrated diethyl ether solution of 1 at low temperature.…”
Section: Resultsmentioning
confidence: 99%
“…1 H and 13 C NMR spectra of 1 in [D 6 ]benzene indicated the chemical equivalence of all six methyl groups due to symmetry (C 3v ) and free rotation of the dimethylamide ligands. In previous studies, WN x nanoparticles were synthesized at high temperature by thermolysis, [61,62] pulsed laser-ablation, [63] and a "urea glass" technique. Compound 1 adopts a pseudo-tetrahedral geometry, as can be seen in the ORTEP representation ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding this, the preparation of nano-sized NbC has been addressed by a lot of researchers to increase active sites per weight on the catalysis. 6,[21][22][23][24][25][26][27][28][29][30][31][32] Recently, Tour and Zhao et al synthesized NbC nanoparticles with ca. 20 nm of size via novel ash Joule heating in the reactor composed of capacitor banks, electrodes, quartz and a carbon source.…”
Section: Introductionmentioning
confidence: 99%